Rôle des compétences sociales et sens de leur interactivité dans la formation : quelles implications pour la recherche et les pratiques pédagogiques ? - Jean-Pierre Abbet (Éducation et Socialisation)
In a context in which it is a lively topic in educational research, the question of taking into account – at both lower secondary and high school level – the learner’s social skills is arised and exemplified in this paper. The goal is to promote their integration into the educational system and into their future social and vocational lives. A few reference points introduce first at recent conceptions or approaches in this field. Regarding these issues, the roles and the stakes of such skills are then pointed as the theoretical frame of a survey carried out in Switzerland (state of Vaud). Afterwards, the characteristics of the selected social skills are specified and these skills are precisely defined. On a basis of empirical findings already published – and bearing in mind that this question directly involve the line of questionning learners – the implications of inherent interactive component of social skills are finally stated and discussed.